2020
DOI: 10.1371/journal.pone.0227245
|View full text |Cite|
|
Sign up to set email alerts
|

Oral misoprostol, low dose vaginal misoprostol, and vaginal dinoprostone for labor induction: Randomized controlled trial

Abstract: Objective To compare effectiveness and safety of oral misoprostol (50 μg every four hours as needed), low dose vaginal misoprostol (25 to 50 μg every six hours as needed), and our established dinoprostone vaginal gel (one to two mg every six hours as needed) induction. Materials and methods Consenting women with a live term single cephalic fetus for indicated labor induction were randomized (3N = 511). Prior uterine surgery or non-reassuring fetal surveillance were exclusions. Concealed computer generated rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 49 publications
0
26
0
Order By: Relevance
“…On the other hand, in the studies by Yehia et al [20], no statistical differences were observed in the occurrence of uterine hyperstimulation in the groups of women undergoing induction with misoprostol and dinoprostone, which may be due to differences in the form and dose of drugs used: titrated oral misoprostol (20 mcg every 2 hours) and vaginal dinoprostone (3 mg). Other studies compared oral misoprostol (50mcg every 4 hours), vaginal misoprostol (25-50mcg every 6 hours) with vaginal gel dinoprostone [23] or vaginal insert dinoprostone (10 mg) [9]. In all the studied groups, the authors did not find statistically significant differences in the occurrence of tachysystole and uterine hyperstimulation.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…On the other hand, in the studies by Yehia et al [20], no statistical differences were observed in the occurrence of uterine hyperstimulation in the groups of women undergoing induction with misoprostol and dinoprostone, which may be due to differences in the form and dose of drugs used: titrated oral misoprostol (20 mcg every 2 hours) and vaginal dinoprostone (3 mg). Other studies compared oral misoprostol (50mcg every 4 hours), vaginal misoprostol (25-50mcg every 6 hours) with vaginal gel dinoprostone [23] or vaginal insert dinoprostone (10 mg) [9]. In all the studied groups, the authors did not find statistically significant differences in the occurrence of tachysystole and uterine hyperstimulation.…”
Section: Discussionmentioning
confidence: 89%
“…A randomized clinical trial is currently in progress regarding efficacy and safety of administering oral misoprostol by titration compared to vaginal misoprostol and dinoprostone for cervical ripening and induction of labor [24]. Most studies reports do not show any increased risk of side effects of misoprostol compared to dinoprostone, as well as worse birth condition of the newborns, longer stay on NICU admission and higher neonatal mortality after induction of labor with misoprostol or dinoprostone [20,22,23,25]. In randomized studies of PLOS ONE -the median birth status of newborns on the Apgar scale at the first and fifth minutes of life did not differ significantly in the groups of mothers induced with prostaglandin analogues: oral or vaginal misoprostol and vaginal dinoprostone [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Young et al found no significance in the parity in the two groups and for the time and the outcome of delivery. 18 Among the patients who received the induction orally, 24% of them required 2 doses followed by 22% who needed 4 doses. Among the patients with vaginal induction, 40% needed only 2 doses.…”
Section: Resultsmentioning
confidence: 99%
“…Established indications for induction include post-term pregnancy, pre-labor membrane rupture (PROM), and maternal hypertension. 1 The use of misoprostol results in a shorter induction to delivery time, a reduction in rate of caesarean section and without any adverse effect on the mother and the neonatal outcomes. It is rapidly absorbed and is more effective than oxytocin or dinoproston for induction of labour.…”
Section: Introductionmentioning
confidence: 99%